Thermo-temporal parametres and slugs structure for thixocasting of hypercutectic silumins - E. I. Marukovich; V. Ju. Stetsenko; S. L. Radko (Литьë и металлургия)
There are given the results of thermo-temporal processing of slugs for thixocasting of hypercutectic silumin. The principle possibility of thixocasting of hypercutectic silumins with inverted structure is shown.